Pelaksanaan Tugas Guru di Sekolah Menengah Kejuruan Negeri Se-Kota Padang - Utami, Suchi; Sulastri, Sulastri (Lembaga Yasin AlSys, 2023)
This research is motivated by the results of observations conducted by the author during observations at the State Vocational High School (SMK Negeri) in Padang City, which showed indications of the suboptimal implementation of teacher duties. The aim of this research is to obtain data and information regarding how well the teacher duties are carried out at the State Vocational High School in Padang City, as seen from several aspects: 1) lesson planning, 2) lesson delivery, 3) assessment of learning outcomes, and 4) implementation of follow-up programs. Therefore, the problem to be addressed in this research is,